The Effect of Brand Trust and Customer Relationship Management on Customer Loyalty with Brand Image as a Mediating Variable in Pelindo Lembar Stevedoring Services - Tariyansah, Agus; Athar, Handry Sudiartha; Supryadi, Didy Ika (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to determine and analyze the role of brand image as a mediating variable in the influence of brand trust and customer relationship management on customer loyalty in Pelindo lembar stevedoring services. This type of research is associative causal. The method used in this study is a census sample. The population in this study were all customers of Pelindo lembar stevedoring services. The analysis tool used is SmartPLS version 4. The result of this study establish several key relationships between brand trust, customer relationship management, brand image, and customer loyalty. The analysis indicates that both brand trust and effective customer relationship management are significant, positive determinants of customer loyalty. These two factors also exert a substantial positive influence on brand image. Furthermore, the investigation confirmed that a favorable brand image directly and significantly enhances customer loyalty. When examining indirect influences, the research identified brand image as a significant mediator for the effect of customer relationship management on customer loyalty. In contrast, while the connection from brand trust to customer loyalty through the lens of brand image was positive, this particular mediating pathway was not found to be statistically significant